Syntactic Analysis of Hiligaynun Visayan: Select Print Media Articles - Evalyn Pedrosa (Philippine Association of Institutions for Research, Inc., 2021)
This study investigates the syntactic structuration of the five select Hiligaynun Visayan Print Media Articles, namely: three news articles such as WANTED PERSON SA ANTIQUE, PRISU, LALAKI GINSIRBIHAN WARRANT, 4- KA TU-IG NGA BATA NALUMUS SA SUBA, and two editorials: SWILDU SANG MANUNUDLU and SAKA SA KUNTRIBUSYUN SA SSS. The study focuses on the following linguistic aspects (1) Immediate Constituents Analysis of the sentences, (2) phrase structures of the syntactic forms, and (3) pedagogic grammar monograph on Visayan Hiligaynun Syntax. The syntactic analysis through Immediate Constituents was the method used for the structuration segments of the articles. The sentences were analyzed using the constituent analysis to reveal syntactic structuration. ICA (Immediate Constituent Analysis) has two phases: phase one, identifying immediate constituents, and phase two, the rule in determining the syntactic structure. Based on the ICA and phrase structures of the sentences, the following are the findings: The ICA of the articles reveals that out of the nineteen sentences, eight are composed of simple sentences, eight compound sentences, and three compound-complex sentences. The syntactic structure phrasal analyses of the five articles yield nineteen sentences consisting of noun phrases, verb phrases, and prepositional phrases. A pedagogic grammar on Hiligaynun Visayan syntax is developed to guide the teaching and learning of Hiligaynun.